P-fractional Kirchhoff equations involving critical nonlinearities. (June 2017) - Fiscella, Alessio; Pucci, Patrizia
Abstract: The paper deals with Kirchhoff type equations on the whole space R N, driven by the p -fractional Laplace operator, involving critical Hardy–Sobolev nonlinearities and nonnegative potentials. We present different variational approaches to overcome the lack of compactness at critical levels, due to the presence of critical terms as well as the possibly degenerate nature of the Kirchhoff problem.